2019
DOI: 10.2147/vhrm.s188089
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Validation of two automatic devices, Omron HEM-6232T and HEM-6181, for self-measurement of blood pressure at the wrist according to the ANSI/AAMI/ISO 81060-2:2013 protocol and the European Society of Hypertension International Protocol revision 2010</p>

Abstract: ObjectiveThe performance of Omron HEM-6232T and Omron HEM-6181 for monitoring blood pressure (BP) at the wrist was validated in accordance with the ANSI/AAMI/ISO 81060-2:2013 protocol (ANSI/AAMI/ISO) and the European Society of Hypertension International Protocol revision 2010 (ESH IP2).MethodsThree trained medical technologists validated the performance of these devices by comparing data obtained from these devices with those obtained using a standard mercury sphygmomanometer.ResultsThe mean differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There are authors who opt for other wrist devices of the same type [ 33 , 35 , 38 , 44 , 50 , 61 ] and therefore do not have rubber tubes. These are more applicable to obese subjects because they have a larger arm circumference, giving erroneous measurement results if a standard upper cuff is used [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are authors who opt for other wrist devices of the same type [ 33 , 35 , 38 , 44 , 50 , 61 ] and therefore do not have rubber tubes. These are more applicable to obese subjects because they have a larger arm circumference, giving erroneous measurement results if a standard upper cuff is used [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the validation team, it also follows the rules of the protocols [ 27 , 29 ], reflected in Table 1 , so it usually corresponds to two observers and a supervisor, except for others that have additional explanations, such as teams formed by three licensed physicians [ 32 , 48 , 58 ], three nurses [ 47 , 55 ], four physicians [ 49 ], or three medical technologists [ 50 , 59 ]. All teams were trained in BP measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In protocol 1, wrist BP at a rest sitting position was measured by a wrist-cuff oscillometric automated BP monitor (Omron HEM-6183, Japan) and it was compared with BP measured on the same upper arm by an oscillometric automated device (Omron HEM-7130-HP, Japan) and also compared with BP measurement on the upper arm by the classical auscultatory method using a mercury sphygmomanometer (Navis 0610-B009, Japan). The accuracies of the same oscillometric device and a device similar to those used in this study have been reported by international standard protocols (Saito, Hishiki, & Takahashi, 2019;Takahashi, Yoshika, & Yokoi, 2015). For wrist BP measurement, a cuff of a single (13.5-21.5 cm) attached to the main body of the device (wrist-cuff device) was used.…”
Section: Study Design and Bp Measurementmentioning
confidence: 97%